Enhancing adaptations to peripheral distractors during basketball throwing in real world through virtual reality application - Pastel, Stefan; Steinert, Marvin; Schwadtke, Alexander; Birkenfeld, Luca; Bürger, Dan; Witte, Kerstin (Frontiers in Virtual Reality, 2025)
IntroductionThe role of sensory distractors has been understudied, particularly in the context of training the sensory system to filter essential information during motor performances. In sports, many distracting peripheral stimuli can disturb an athlete’s optimal performance, such as an opponent attempting to block a throw or disrupt walking paths. This study investigated whether Virtual Reality (VR) technology could mitigate such influences by creating a virtual training scenario involving a basketball throwing task.Methods54 participants were divided into three groups who underwent different training: one group trained in the real world (RW_G), another that trained in a virtual environment (VR_G), both with an opponent, and a third group (RW_WO) trained in the real world (RE) without an opponent. The RW_WO group was excluded from the main analysis, as it did not fulfill the necessary prerequisites, which are described later. Pre- and post-tests were conducted to assess whether the participants improved performance by reducing the disturbance effect of the opponent. A self-defined scoring system was used to quantify the participants’ performances, which was compared across different throwing conditions (with and without opponent’s impact). A three-way ANOVA with repeated measurements with Bonferroni-corrected post hoc tests was conducted, including the between-subject factor group [RW_G, VR_G] and the within-subject factors Time [Pretest, Posttest] and Condition [with and without opponent].ResultsNo significant interaction of Time*Condition*Group was found between the groups RW_G and VR_G (p = 0.552), indicating similar habituation to the opponent after VR and RW sensory training. In the posttest, no significant differences existed between conditions (with and without opponent) were observed in either group.DiscussionVR training can match the effectiveness of training in real-world conditions. However, its benefits appear to be limited to participants who were genuinely affected by an opponent attempting to block the throw (beginners). The role of distractive stimuli is discussed, and possible future implementations are suggested.